The effect of hinged supracondylar knee ankle foot orthosis on gait parameters in children with spastic cerebral palsy having knee hyperextension and ankle equinus - Sahoo, Ullas Chandra; Sahoo, Smrutiprava (International Journal Of Community Medicine And Public Health, 2022)
Background: In cerebral palsy, importance must be given on effective and efficient walking. 30 subjects; 16 males and 14 females (mean age 6.5 year) of spastic cerebral palsy with knee hyperextension and ankle equines were included in this study and were fitted with bilateral moldedhinged SKAFO with pair of shoes. Methods: Observational gait analysis by video recording was performed and gait parameters by 10 m walk test and knee angle at mid stance using goniometer in standing position were recorded in bracing and non-bracing conditions. Results: The orthosis controlled knee hyperextension by not restricting normal flexion and extension moment with smooth transition of ankle motion. There was significant improvement in step length; stride length as well as knee angle at midstance (with orthosis) but velocity and cadence were reduced as compared to bare foot walking. Conclusions: A stable, natural and controlled knee hyperextension gait pattern was found.